A multimodal aftercare intervention improves the outcome after kidney transplantation – results of the KTx360° aftercare program using claims data - Pape, Lars; DeZwaan, Martina; Nöhre, Mariel; Klewitz, Felix; Kyaw Tha Tun, Eva; Prüfe, Jenny; Schiffer, Lena; Gertges, Raoul; Schieffer, Elisabeth; Albrecht, Alexander; Boeck, Hedwig Theda; Kliem, Volker; et al. (EClinicalMedicine, 2024)
Background: The after-care treatment project KTx360° aimed to reduce graft failure and mortality after kidney transplantation (KTx). Methods: The study was conducted in the study centers Hannover, Erlangen and Hannoversch Muenden from May 2017 to October 2020 under the trial registration ISRCTN29416382. The program provided a multimodal aftercare program including specialized case management, telemedicine support, psychological and exercise assessments, and interventions. For the analysis of graft failure, which was defined as death, re-transplantation or start of long-term dialysis, we used longitudinal claims data from participating statutory health insurances (SHI) which enabled us to compare participants with controls. To balance covariate distributions between these nonrandomized groups we used propensity score methodology, in particular the inverse probability of treatment weighting (IPTW) approach. Findings: In total, 930 adult participants were recruited at three different transplant centres in Germany, of whom 320 were incident (enrolled within the first year after KTx) and 610 prevalent (enrolled >1 year after KTx) patients. Due to differences in the availability of the claims data, the claims data of 411 participants and 418 controls could be used for the analyses. In the prevalent group we detected a significantly lower risk for graft failure in the study participants compared to the matched controls (HR = 0.13, 95% CI = 0.04–0.39, p = 0.005, n = 389 observations), whereas this difference could not be detected in the incident group (HR = 0.92, 95% CI = 0.54–1.56, p = 0.837, n = 440 observations). Interpretation: Our findings suggest that a multimodal and multidisciplinary aftercare intervention can significantly improve outcome after KTx, specifically in patients later after KTx. For evaluation of effects on these outcome parameters in patients enrolled within the first year after transplantation longer observation times are necessary. Funding: The study was funded by the Global Innovation fund of the Joint Federal Committee of the Federal Republic of Germany, grant number 01NVF16009.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Adherence; Cardiovascular risk; Case-management; Graft survival; Kidney transplantation; Physical activity